Aldosteronism and Resistant Hypertension - Maria Czarina Acelajado; David A. Calhoun (International Journal of Hypertension)
Resistant hypertension (RHTN) is defined as blood pressure (BP) that remains uncontrolled in spite of intake of ≥3 antihypertensive medications, ideally prescribed at optimal doses and one of which is a diuretic. The incidence of primary aldosteronism (PA) in patients with RHTN is estimated in prospective studies to be 14 to 23%, which is higher than in the general hypertensive population. Patients with PA are at an increased cardiovascular risk, as shown by higher rates of stroke, myocardial infarction, and arrhythmias compared to hypertensive individuals without PA. Likewise, RHTN is associated with adverse cardiovascular outcomes, and the contribution of PA to this increased risk is undetermined. Similar to PA, obstructive sleep apnea (OSA) is closely associated with RHTN, and a causal link between PA, OSA, and RHTN remains to be elucidated. The addition of MR antagonists to the antihypertensive regimen in patients with RHTN produces a profound BP-lowering effect, and this effect is seen in patients with or without biochemical evidence of PA, highlighting the role of relative aldosterone excess in driving treatment resistance in this group of patients.